2021
DOI: 10.18421/tem101-12
|View full text |Cite
|
Sign up to set email alerts
|

Readiness Model in Adopting E-health: An Indonesian Experience

Abstract: This study aims to investigate e-health use in some hospitals in Indonesia through the readiness model. The readiness factor identified as the core, societal, technological and engagement readiness also expected efforts. The research model measured the influence of the readiness factors on e-health adoption and their impact on performance. A-104 respondent of e-health user among hospitals across Indonesia were obtained accidentally in the e-survey technique. The data was analysed to test six hypotheses using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The electronic readiness of the system is identified as the electronic readiness of the practitioner, the organization and the public to adopt e-Health systems [6], [7]. Certain indicators are used to measure this readiness, including needs identification, dissatisfaction, awareness, technology compliance, trust, planning, integration and overall satisfaction [6], [8].…”
Section: Methodology and Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic readiness of the system is identified as the electronic readiness of the practitioner, the organization and the public to adopt e-Health systems [6], [7]. Certain indicators are used to measure this readiness, including needs identification, dissatisfaction, awareness, technology compliance, trust, planning, integration and overall satisfaction [6], [8].…”
Section: Methodology and Algorithmsmentioning
confidence: 99%
“…The use of electronic health systems can lead to the establishment of a new structure -through standardization, medical systems and their impact on the quality of health care, reducing health care costs and more [5], [6]. There are many initiatives related to e-Health systems, including practice planning, information source and sharing, service delivery (for chronic diseases), remote care management, support for clinical solutions in interdisciplinary diagnosis, treatment and care processes, electronic health card and public health research and prevention [3].…”
Section: Introductionmentioning
confidence: 99%
“…e-Health uses information and communication technologies for diagnosing and treating patients and promoting a healthy lifestyle (primary prevention), conducting research, training health professionals, tracking diseases and monitoring public health to improve or create conditions for provision of health services and health care [21], [22], [23].…”
Section: е-Healthmentioning
confidence: 99%
“…According to the evaluation using FL, the SEM-PLS analysis has determined that the research model has satisfactorily achieved discriminant validity, as suggested by the findings-additionally, the values of CR and CA for each variable. This research utilizes a tool that has been validated and is deemed reliable, as evidenced by the model surpassing the benchmark threshold of 0.7 [8], [49]. The correlation coefficients capture the distinctiveness of each variable in the technology acceptance framework, which is vital for evaluating discriminant validity.…”
Section: A Measurement Modelmentioning
confidence: 99%
“…This sector contributes substantially to the GDP and plays a crucial role in addressing human resource challenges, such as poverty. The statistics provided by the Badan Pusat Statistik (Indonesia Central Bureau of Statistics) show a steady rise in the workforce of MSMEs, which escalated to 114,144,082 between 1997 and 2020, along with a notable impact on the growth of the GDP [8]. In response to the industry 4.0 era, MSMEs must integrate advanced technologies, a process facilitated by governmental efforts such as the MSME Go Online initiative.…”
Section: Introductionmentioning
confidence: 99%